Multi-compartment immune cell profiling highlights the prognostic relevance of CD127+ CD8+ T cells for patients with high-grade serous ovarian cancer - Rothe, Rebecca; Tunger, Antje; Link, Theresa; Lai, Xixi; Kuhlmann, Jan Dominik; Wimberger, Pauline; Schmitz, Marc; Wehner, Rebekka (Frontiers in Immunology, 2025)
Ovarian cancer (OC) is a heterogeneous tumor entity with accumulated ascitic fluid in the peritoneal cavity, especially in advanced tumors. In general, a high immune cell infiltration has a favorable effect on OC patients’ outcomes. However, the composition of immune cells within the individual compartments of OC-associated locations may differ in their impact on patient prognosis. Therefore, we comprehensively investigated immune cell frequencies in matched peripheral blood, ascites, and tumor samples of 24 high-grade serous OC patients by flow cytometry and associated them with clinical parameters. Immune cell analysis demonstrated that the general immune cell infiltration was comparable between the three investigated compartments, with decreased proportions of CD8+ T cells in advanced stage OC. In addition, immune cell subsets varied significantly in their differentiation and phenotypic marker expression. In peripheral blood, classical monocytes, mature natural killer (NK) cells with cytotoxic potential (CD57+, CD16+, NKG2D+), and less differentiated T cells were more frequent. On the contrary, dendritic cells, and NKp46+ NK cells were prevalent in ascites. In OC tissues, high frequencies of immature neutrophils, CD16- NK cells, and effector memory T cells were found, although the intratumoral T cell frequency was significantly reduced compared to the two liquid samples. Additionally, T cell profiling showed high expression of one or multiple activating and inhibitory receptors in tumor samples. In particular, significant positive correlations of CD127+ CD8+ T cells among all three compartments were shown. Our results provide evidence that a higher proportion of peripheral CD127+ CD8+ T cells, which are memory T cells with low granzyme B production, was a prognostic biomarker for unfavorable progression-free survival of high-grade OC patients, independent of FIGO stage III/IV or residual tumor after surgery.